2017
DOI: 10.1038/s41598-017-16165-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep Deprivation Diminishes Attentional Control Effectiveness and Impairs Flexible Adaptation to Changing Conditions

Abstract: Insufficient sleep is a global public health problem resulting in catastrophic accidents, increased mortality, and hundreds of billions of dollars in lost productivity. Yet the effect of sleep deprivation (SD) on decision making and performance is often underestimated by fatigued individuals and is only beginning to be understood by scientists. The deleterious impact of SD is frequently attributed to lapses in vigilant attention, but this account fails to explain many SD-related problems, such as loss of situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…Besides, and more importantly, these ASD-related behavioral modifications were associated with a decrease of cognitive flexibility. These results match previous ones showing that ASD is responsible for perseverative behaviors in humans [ 6 , 8 , 9 ]. Our control experiments ruled out the effect of stress related to ASD, as plasma corticosterone measures did not show any difference between control and ASD mice.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, and more importantly, these ASD-related behavioral modifications were associated with a decrease of cognitive flexibility. These results match previous ones showing that ASD is responsible for perseverative behaviors in humans [ 6 , 8 , 9 ]. Our control experiments ruled out the effect of stress related to ASD, as plasma corticosterone measures did not show any difference between control and ASD mice.…”
Section: Discussionsupporting
confidence: 92%
“…Healthy human subjects with normal sleep were recruited to the Sleep and Performance Research Center at Washington State University Spokane. Subjects met inclusion criteria described by us previously [ 66 ]. They had no current cancer or history of cancer, chemotherapy treatment, or radiation treatment.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study confirmed that homozygous carriers of the C allele of the DRD2 c.957C>T polymorphism are impaired by sleep deprivation in vigilant attention (Whitney et al, 2017). Remarkably, however, the same individuals were resilient to the effects of prolonged waking on reversal learning, a measure of cognitive flexibility (Whitney et al, 2017). Consistent with the notion that the consequences of sleep deprivation are trait-like but task-specific, the data collectively suggest that striato-thalamo-cortical dopaminergic pathways contribute to the regulation of neurophysiological and neurobehavioral consequences of sleep loss in humans.…”
Section: Drd2 Genotype Modulates Neurophysiological and Neurobehaviormentioning
confidence: 83%
“…More specifically, individuals homozygous for the C allele of DRD2 and the 10R allele of DAT1 were more severely affected with attentional lapses after 40 hours of wakefulness than other genotypic variants. A recent study confirmed that homozygous carriers of the C allele of the DRD2 c.957C>T polymorphism are impaired by sleep deprivation in vigilant attention (Whitney et al, 2017). Remarkably, however, the same individuals were resilient to the effects of prolonged waking on reversal learning, a measure of cognitive flexibility (Whitney et al, 2017).…”
Section: Drd2 Genotype Modulates Neurophysiological and Neurobehaviormentioning
confidence: 92%
See 1 more Smart Citation